2018
DOI: 10.4070/kcj.2017.0179
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Pediatric Multifocal Atrial Tachycardia and Its Prognostic Factors

Abstract: Background and ObjectivesMultifocal atrial tachycardia (MAT), in general, has a favorable outcome. However, there are insufficient data regarding MAT in a pediatric population. This study sought to determine the clinical course of MAT and identify potential prognostic factors.MethodsThe medical records of MAT patients from 1997–2015 were reviewed. The arrhythmia control rate and factors for unfavorable outcomes were assessed and compared to those in the literature.ResultsOf the 33 included patients (19 boys an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The vast majority of children with multifocal atrial tachycardia present under a year of age with 24-43% having some associated respiratory illness. 1,2 In a series of 21 patients (median age 1.8 months) with multifocal atrial tachycardia, Bradley reported that 27% had diminished ventricular function with two being critically ill. 1 A variety of anti-arrhythmic medications were utilised with a mixed response though the natural history was fairly favourable with 52% in sinus rhythm within 5 months and 94% asymptomatic and free of any arrhythmia by 60 months. 1 This is in contradistinction to our patient who presented at a slightly older age, 5 months, in extremis and required advanced mechanical circulatory support.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of children with multifocal atrial tachycardia present under a year of age with 24-43% having some associated respiratory illness. 1,2 In a series of 21 patients (median age 1.8 months) with multifocal atrial tachycardia, Bradley reported that 27% had diminished ventricular function with two being critically ill. 1 A variety of anti-arrhythmic medications were utilised with a mixed response though the natural history was fairly favourable with 52% in sinus rhythm within 5 months and 94% asymptomatic and free of any arrhythmia by 60 months. 1 This is in contradistinction to our patient who presented at a slightly older age, 5 months, in extremis and required advanced mechanical circulatory support.…”
Section: Discussionmentioning
confidence: 99%
“…Baek et al 6) reported the clinical outcome of MAT and potential prognostic factors. Compared to the previous reports, this study has relatively large number of patients and composed of various etiologies despite of limitation of retrospective study from single tertiary center.…”
mentioning
confidence: 99%
“…RASopathy has been reported to be associated with high incidence of atrial arrhythmias. 6) 7) MAT in children should be checked the association of RASopathy and vice versa.…”
mentioning
confidence: 99%
See 2 more Smart Citations